GOODBYE TO AFGHANS - Sayed Qudrat Hashimy (International Journal of Law in Changing World, 2024)
The Genealogies of complicity and struggle between Afghanistan and Pakistan date back to a single-page Agreement of 1893 (Duran line) and the invasion of the Union of Soviet Socialist Republics (USSR) in 1979. The squabble of the World towards Pakistan with its inglorious policy to deport undocumented 1.7 million refugees to a war-stricken country is inhuman and wrong and leaves them as political pawns. The Mass Exodus of Afghan Refugees and the anti-immigrant policy of Pakistan trigger some legal questions: Why is Pakistan deporting Afghans at this point? Who hears the voice of suffering at the dark noon? What happens next to these deportees? The existing article is poignant in examining the status of human rightslessness of sans-papiers under the human rights paradigm in Pakistan. In tandem with this, the paper also discusses the human rights dimension from the lens of the perplexing situation that prevails in Afghanistan. This article is percolated by axiomatic development in the theory and practice of human rights supplanted by wretched migrants. Thus, this paper offers a series of fragments of thought concerning some ways of understanding the changing human rights paradigms in Afghans.